The effect of ellagic acid on performance, digestibility, egg quality, cecal bacterial flora, antioxidant activity, and some blood parameters in laying quails reared at different temperatures - Iflazoglu Mutlu, Seda; Guler, Talat (Tubitak Scientific & Technological Research Council Turkey, 2021)
In this study, the effect of ellagic acid on the performance, egg quality, digestibility, cecal microflora, serum malondialdehyde (MDA) level, and biochemical parameters in quails reared under normal conditions and at high environmental temperatures was investigated. The animals (n = 240; 5-weeks old) reared at 2 environmental temperatures [thermoneutral (TN) and heat stress (HS)] and in 4 diet groups containing different ellagic acid doses (0, 100, 200, and 400 mg/kg) were randomly assigned to 8 groups according to the 2 x 4 factorial design. Feed intake, egg weight, and egg production were higher (P < 0.001) and feed conversion (P < 0.01) was better in the TN groups compared to the HS groups. Egg (P < 0.01) and shell weights (P < 0.001) were higher in the TN groups compared to the HS groups. The effect of ellagic acid supplementation on shell weight was statistically significant in the TN and HS groups (P < 0.05). The effects of environmental temperature and the supplementation of ellagic acid on digestibility of dry matter (P < 0.05), ether extract (P < 0.01), and crude protein (P < 0.01) were statistically significant in the TN and HS groups. Supplementation of ellagic acid reduced the total coliform bacteria count (P < 0.01) and increased the total lactic acid bacteria count (P < 0.001) in the cecum. Serum MDA levels increased with heat stress (P < 0.001) and decreased with the supplementation of ellagic acid (P < 0.001). The effect of environmental temperature on serum glucose (P < 0.001), cholesterol (P < 0.05), total protein (P < 0.05), alanine aminotransferase (ALT) (P < 0.001), sodium (P < 0.05), and magnesium was significant. In conclusion, the supplementation of ellagic acid decreased oxidative stress and total coliform bacteria count and improved the feed conversion and egg quality in quails under heat stress. Moreover, ellagic acid increased the digestibility of nutrients and had a positive effect on lactic acid bacteria. It was observed in this study that these beneficial effects of ellagic acid increased with an increasing dose, and 400 mg/kg was the most effective dose.
Keywords: Ellagic acid; performance; egg quality; digestibility; microflora; malondialdehyde